PERANCANGAN SISTEM E-VOTING DALAM PEMILIHAN OSIS PADA SMK YAPIM TARUNA MARELAN - Randi Rian Putra (Jurnal Abdi Ilmu, 2021)
With the development of technological advances that greatly affect the development of information in an educational or academic field and in various other fields, one of which is the selection of student councils in schools during the covid 19 pandemic. The election of student council leaders is something we have often done in junior high and vocational / high school but because still manual, often slows down the process of selecting the student council chairman. During the pandemic, the teaching and learning process will continue to be carried out online or online as well as the selection of the student council chairman and his deputy, Smk Yapim Taruna Marelan is a high school that wants to realize the technology development process to improve quality and quality. Therefore, the author wants to build a website-based online system, in order to make it easier for employees and students at Smk Yapim Taruna Marelan to speed up the processing of data on the results of the vote. In order to be easily accessed by other teachers and students to choose the student council chair, anywhere and anytime the Yapim Taruna Marelan Vocational School can access this system as long as it is connected to the internet.